2015
DOI: 10.1371/journal.pone.0130393
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Germline Mutations in Genes Engaged in DNA Damage Repair by Homologous Recombination in Patients with Triple-Negative and Hereditary Non-Triple-Negative Breast Cancers

Abstract: PurposeThis study sought to assess the prevalence of common germline mutations in several genes engaged in the repair of DNA double-strand break by homologous recombination in patients with triple-negative breast cancers and hereditary non-triple-negative breast cancers. Tumors deficient in this type of DNA damage repair are known to be especially sensitive to DNA cross-linking agents (e.g., platinum drugs) and to poly(ADP-ribose) polymerase (PARP) inhibitors.MethodsGenetic testing was performed for 36 common … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 61 publications
(92 reference statements)
0
24
0
Order By: Relevance
“…Data from the literature argue that CHEK2 mutations are associated with ER-positive types according to a study from 2009 conducted on Polish population [23], which is supported also by a recent article stating that the carriers of CHEK2 mutations associate luminal tumors rather than TNBC [9].…”
Section: Chek2mentioning
confidence: 75%
See 1 more Smart Citation
“…Data from the literature argue that CHEK2 mutations are associated with ER-positive types according to a study from 2009 conducted on Polish population [23], which is supported also by a recent article stating that the carriers of CHEK2 mutations associate luminal tumors rather than TNBC [9].…”
Section: Chek2mentioning
confidence: 75%
“…However, knowing the association of BRCA1 mutations with TNBC can open new opportunities for treatment using the platinum agents or poly ADP ribose polymerase inhibitors (PARP inhibitors) [9].…”
Section: Introductionmentioning
confidence: 99%
“…Many other BRCA1/2--wild-type TNBCs occur as sporadic tumors that share traits with germline BRCA-mutated tumors and are termed to have BRCAness (39,40). For example, analysis of germline mutations in 158 TNBC patients demonstrated that in addition to BRCA1 mutations (17% of patients), mutations of the CHEK2 checkpoint kinase 2 gene, nibrin NBN gene, and ATM genes also were found (3.9%), and are themselves involved in various aspects of the HRR pathway (41)(42)(43). Overall, the evidence suggests that besides BRCA1/2 status, many other genes contribute to the BRCAness of TNBC.…”
Section: Discussionmentioning
confidence: 99%
“…Table 3A and 3B summarizes the primary aim of these studies, the inclusion criteria, the list of genes included in the selected panels and the results of ten published studies that included more than 500 patients who had undergone diagnostic multigene panel testing for HBOC [18-20, 22-23, 25, 27-28, 30-31]. One study was excluded from this review despite the high number of patients, because the authors chose to study only 36 known pathogenic mutations in the selected HBOC genes [14]. The highest number of patients included was 10030, most of whom had HBOC, although one study was limited to unselected TNBC patient [31] and another one to OC [29].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of these genes are part of the DNA repair/BRCA pathway [13][14][15][16]. NGS has made it possible for clinicians to order a single test that evaluates multiple genes simultaneously in a cost-effective and efficient fashion, thus enabling a more complete genetic evaluation [17].…”
Section: Introductionmentioning
confidence: 99%